Architecture and Pipeline for Automating ELLAS Network Knowledge Network Governance - Fritoli, Rodgers (2023)
In this article, a proposed architecture for integrating knowledge graphs and a pipeline that automates the transformation of spreadsheet data into RDF triple knowledge graphs for the open data platform of the ELLAS research network is described. The main goal of the ELLAS research network project is to generate comparable data on gender gaps in STEM in Latin America, and since the data comes from various sources and formats, semantic web will be used to add meaning to the data. The architecture and pipeline proposal is to perform Extract, Transform, and Load (ETL) activities for data storage and availability to end users.